Feeding Ecology of Taruca (Hippocamelus antisensis) Populations during the Rainy and Dry Seasons in Central Peru - Carla Gazzolo; Javier Barrio (International Journal of Zoology)
Tarucas (Hippocamelus antisensis) live in rocky areas in the Andes, from northern Peru to northern Argentina. Microhistological analyses on their feeding ecology during the rainy and dry seasons were done at a National Park and a Landscape Reserve. The diet was diverse and more than 50 species were identified from the feces. Grass species were most often detected as eaten by taruca during the rainy season comprising near 70% of the consumed fragments with 35 plant species identified as eaten then. In the dry season, around 50 species were identified as eaten by tarucas, mostly dicotyledonous. The main species consumed in both seasons were Werneria nubigena, Poa gymnantha, Senecio comosus, and Ephedra americana. The ecological density was an intermediate value compared to other observed values in Peru. This is the first study to find the importance of grasses for tarucas, selected when soft, during the rainy season. A possible overlap with domestic ungulates’ diets should be explored, helping the conservation of taruca and generating an adequate management of the species and the ecosystem. There is a change in the palatable offer of food items during the rainy season, when most of the Gramineae species are tender.